Quantum oscillations from the reconstructed Fermi surface in electron-doped cuprate superconductors. (12th April 2018) - Higgins, J S; Chan, M K; Sarkar, Tarapada; McDonald, R D; Greene, R L; Butch, N P
Abstract: We have studied the electronic structure of electron-doped cuprate superconductors via measurements of high-field Shubnikov–de Haas oscillations in thin films. In optimally doped Pr2− x Ce x CuO4± δ and La2− x Ce x CuO4± δ, quantum oscillations indicate the presence of a small Fermi surface, demonstrating that electronic reconstruction is a general feature of the electron-doped cuprates, despite the location of the superconducting dome at very different doping levels. Negative high-field magnetoresistance is correlated with an anomalous low-temperature change in scattering that modifies the amplitude of quantum oscillations. This behavior is consistent with effects attributed to spin fluctuations.